Assessment of digital camera in mapping meandering flume using close range photogremmetric technique - Udin, W.S.; Ahmad, A.; Ismail, Z. (Universiti Putra Malaysia, 2014)
In recent years image acquisition in close range photogrammetry relies on digital sensors such as digital cameras, video cameras, CCD cameras etc that are not specifically designed for photogrammetry. This study is performed to evaluate the compatibility of the digital metric camera and non-metric camera for the purpose of mapping meandering flume, using close range photogrammetric technique and further, to determine the accuracy that could be achieved using such a technique. The meandering flume provides an opportunity to conduct an experimental study in a controlled environment. In this study, the digital images of the whole meandering flume were acquired using a compact digital camera - Nikon Coolpix S560, a Single Lens Reflex (SLR) Nikon D60 and also a metric digital camera Rollei D30. A series of digital images were acquired to cover the whole meandering flume. Secondary data of ground control points (GCP) and check points (CP), established using the Total Station technique, was used. The digital camera was calibrated and the recovered camera calibration parameters were then used in the processing of digital images. In processing the digital images, digital photogrammetric software was used for processes such as aerial triangulation, stereo compilation, generation of digital elevation model (DEM) and generation of orthophoto. The whole process was successfully performed and the output produced in the form of orthophoto. The research output is then evaluated for planimetry and vertical accuracy using root mean square error (RMSE). Based on the analysis, sub-meter accuracy is obtained. It can be concluded that the differences between the different types of digital camera are small . As a conclusion, this study proves that close range photogrammetry technique can be used for mapping meandering flume using both the metric digital camera and non-metric digital camera